Error analysis: a case study of Malaysian EFL learners - Alhalawani, Ali Alsayed Hassan (Published by the Future Academy, 2018)
Error analysis is a very significant area of applied linguistics as well as foreign language learning. This study was to identify, describe and explain the errors made by EFL tertiary-level learners in tackling a translation assignment from Malay into English. A class of 38 students of the 3rd and 4th levels constituted the subjects of the study. A period of one week was given to complete the translation task. The answers were thoroughly examined and analysed. Based on the first reading of the answers, it was clear that nearly all types of errors were made. The study focused more on the errors in written English, be it grammatical or collocational, rather than those of a translational or equivalence-based nature. It is hoped that when EFL teachers understand the different types of errors learners make, they will be better able to help learners improve their writing skills and acquire grammar accuracy. Results and implications of the findings are to be discussed further.